A Novel Human Detection Algorithm Based on Foreground Segmentation (Journal of Fiber Bioengineering and Informatics, 2013)
In computer vision applications, human detection occupies an important position. HOG (Histogramsof Oriented Gradient) is a classical algorithm which was used in the area of object detection. But thecomplex background would greatly affect the test accuracy when taking HOG as a human characteristicfor human detection. In order to improve the accuracy of human detection, this paper applied a newalgorithm which was based on foreground segmentation. We could get each closed region by OrientedWatershed Transform and Ultrametric Contour Map, then the foreground and the background could bedistinguished. Finally we removed the background and calculated the foreground characteristic. Theexperimental results show that this approach was effective in improving detection accuracy.
Keywords: Human Detection; HOG; Foreground Segmentation; Closed Region